Perennialism and Divine Education: Sayyed Hossein Nasr, Khosrow Bagheri, and Zohreh Khosravi - Asiyah, Asiyah; Ismail, Ismail; Astuti, Mardiah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aims to examine the continued relevance of perennialism and divine education theories in the context of 21st-century education, which is confronted with a multitude of global, social, and technological challenges. This study employs a qualitative research approach through library research to examine the educational concepts proposed by philosophers Sayyed Hossein Nasr, Khosrow Bagheri, and Zohreh Khosravi. These philosophers emphasize the importance of spiritual, moral, and character dimensions in education, in addition to intellectual aspects. The tenets of Perennialism and Divine Theory posit that authentic knowledge is immutable and unaffected by the vicissitudes of time. They place emphasis on the cultivation of character and spiritual understanding derived from divine teachings. This research analyzes texts related to the thoughts of the three philosophers to understand how education can be integrated with spiritual and divine values in order to form a generation that is not only competent in academic aspects, but also has spiritual and moral depth. The results demonstrate that the application of the concepts of Perennialism and Divine in modern education can help shape individuals who are balanced between intellectual intelligence and high character qualities, making it relevant and important in addressing contemporary educational challenges.